2006
DOI: 10.1590/s0034-72992006000200020
|View full text |Cite
|
Sign up to set email alerts
|

Timpanoplastias: resultados cirúrgicos e análise dos fatores que podem interferir no seu sucesso

Abstract: Chroni c otitis media has a high prevalence on the population and their treatment continuous to be a challenge for the otorhinolaryngologists. Aim: To demonstrate the factors that could interfere in the tympanoplasty success and the surgical results during 2002. Study Design: Clinical prospective. Material and Method: were included 37 patients with chronic otitis media non cholesteatoma (COMNC) undergo to tympanoplasty (in lay or underlay, with homologous graft). All the patients were submitted to a survey pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…18,[29][30][31] Several other studies have found no significant statistical correlation. 4,5,32 in our study, graft integration in patients with dry ears occurred in 94.5% of cases (p=0.254); it was 100% in patients with wet ears (p=0.387). Thus, the status of the ear (dry or wet) was not statistically important for surgical success.…”
Section: Discussionmentioning
confidence: 46%
“…18,[29][30][31] Several other studies have found no significant statistical correlation. 4,5,32 in our study, graft integration in patients with dry ears occurred in 94.5% of cases (p=0.254); it was 100% in patients with wet ears (p=0.387). Thus, the status of the ear (dry or wet) was not statistically important for surgical success.…”
Section: Discussionmentioning
confidence: 46%
“…The hearing thresholds may be influenced by factors such as the size and location of the tympanic perforation, the presence of ossicular chain erosion or disarticulation as well as the presence of cholesteatoma and its growth patterns [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The goals of this study were as follows: (1) to compare air conduction thresholds (AC), bone conduction thresholds (BC) and air-bone gaps in children and teenagers with chronic suppurative otitis media with cholesteatoma (CCOM) and those without cholesteatoma (NCCOM); (2) to compare air-bone gaps between different cholesteatoma growth patterns; (3) to verify the relation between the number of perforated quadrants and the value of the airbone gap; (4) to compare air-bone gaps between posterior quadrant tympanic perforations and anterior quadrant tympanic perforations.…”
Section: Introductionmentioning
confidence: 99%
“…The efferent pathways dysfunction is one of the possible mechanisms causing tinnitus 7 . Tympanoplasties usually improve tonal thresholds [8][9][10][11][12] and the favorable tinnitus results are very likely a consequence of this improvement, since the proper vibration of middle ear fluids re-establishes both afferent and efferent stimuli 13 . This is the classical example of the probable association between hearing improvement and tinnitus improvement that may also be seen in the clinical practice in the postoperative of patients with middle ear effusion, ossicular chain fixation or broken; or external acoustic meatus stenosis Tinnitus improvement after hearing restoration can also be explained by the theory of central auditory pathways hypersensitivity after reduction in afference.…”
Section: Discussionmentioning
confidence: 99%
“…Gerber et al (2000) did a retrospective study of patients submitted to tympanoplasty with tragal cartilage pericondrium or temporal muscle fascia, observing improvements in tonal thresholds and gap, regardless of the type of graft used9. Fukuchi et al (2006) show that graft take does not depend on age, perforation size, graft type, time of disease, among others, despite the low success rate of 65% of graft take, they associated it to the surgeon's skills, since all the procedures were carried out by resident physicians 12 .…”
Section: Discussionmentioning
confidence: 99%